Sediment size fractionation and focusing in the equatorial Pacific: Effect on 230Th normalization and paleoflux measurements. (30th July 2014) - Lyle, Mitchell; Marcantonio, Franco; Moore, Willard S.; Murray, Richard W.; Huh, Chih‐An; Finney, Bruce P.; Murray, David W.; Mix, Alan C.
Abstract: We use flux, dissolution, and excess 230 Th data from the Joint Global Ocean Flux Study and Manganese Nodule Project equatorial Pacific study Site C to assess the extent of sediment focusing in the equatorial Pacific. Measured mass accumulation rates (MAR) from sediment cores were compared to reconstructed MAR by multiplying the particulate rain caught in sediment traps by the 230 Th focusing factor and subtracting measured dissolution. CaCO3 MAR is severely overestimated when the 230 Th focusing factor correction is large but is estimated correctly when the focusing factor is small. In contrast, Al fluxes in the sediment fine fraction are well matched when the focusing correction is used. Since CaCO3 is primarily a coarse sediment component, we propose that there is significant sorting of fine and coarse sediments during lateral sediment transport by weak currents. Because CaCO3 does not move with 230 Th, normalization typically overcorrects the CaCO3 MAR; and because CaCO3 is 80% of the total sediment, 230 Th normalization overestimates lateral sediment flux. Fluxes of 230 Th in particulate rain caught in sediment traps agree with the water column production‐sorption model, except within 500 m of the bottom. Near the bottom, 230 Th flux measurements are as much as 3 times higher than model predictions. There is also evidence for lateral near‐bottom 230 Th transport in the bottom nepheloid layer since 230 Th fluxes caught by near‐bottom sediment traps are higher than predicted by resuspension of surface sediments alone. Resuspension and nepheloid layer transport under weak currents need to be better understood in order to use 230 Th within a quantitative model of lateral sediment transport. Key Points: Weak currents at seafloor preferentially resuspend fine sediments and Th‐230 CaCO3 and other coarse fraction lateral transport is overestimated by Th‐230 Nepheloid layer enriched in excess Th‐230 sedimented by high particle flux